2015
DOI: 10.5688/ajpe799139
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Experiences for Second-Year Student Pharmacists at an Academic Medical Center

Abstract: Objective. To examine student outcomes associated with the Student Medication and Reconciliation Team (SMART) program, which was designed to provide second-year student pharmacists at the University of North Carolina (UNC) Eshelman School of Pharmacy direct patient care experience at UNC Medical Center. Design. Twenty-two second-year student pharmacists were randomly selected from volunteers, given program training, and scheduled for three 5-hour evening shifts in 2013-2014. Pre/post surveys and reflection sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The medication reconciliation process is required to meet Meaningful Use criteria set forth by the Center for Medicare and Medicaid Services, and this took up much of the providers’ appointment time. 7,8 Medical assistants or nurses, if available, usually performed the medication reconciliation, but there was concern for errors due to time constraints. For this reason and its success in the cardiology department, it was recommended that student pharmacists assist in the other departments and the College of Pharmacy was approached for a solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medication reconciliation process is required to meet Meaningful Use criteria set forth by the Center for Medicare and Medicaid Services, and this took up much of the providers’ appointment time. 7,8 Medical assistants or nurses, if available, usually performed the medication reconciliation, but there was concern for errors due to time constraints. For this reason and its success in the cardiology department, it was recommended that student pharmacists assist in the other departments and the College of Pharmacy was approached for a solution.…”
Section: Methodsmentioning
confidence: 99%
“…Although these standards are in regard to APPE, there is evidence that suggests such experiences promote students’ appreciation for the various roles pharmacist play in health care and the complexity of real-world practice prior to their third year of professional school. 7…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of required introductory experiential education to students and institutions have been well documented in the literature (Mort et al, 2010;Walker et al, 2011;Mersfelder & Bouthillier, 2012;Yorra, 2014;Mclaughlin et al, 2015;Stanton et al, 2017;Boyle et al, 2020). For students, IPPEs have shown to increase self-esteem, enhance learning and development, foster an appreciation for pharmacy practice, and provide opportunities to inform career interests (Mort et al, 2010;Walker et al, 2011;Yorra, 2014;Plott et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Available literature demonstrates that required IPPEs are beneficial to students and experiential sites, however, the impact of IPPE hours that exceed ACPE requirements has not been previously documented (Mort et al, 2010;Walker et al, 2011;Mersfelder & Bouthillier, 2012;Yorra, 2014;Mclaughlin et al, 2015;Stanton et al, 2017;Boyle et al, 2020). The study sought to determine why students chose to take elective IPPEs and what aspects of these rotations were perceived to be most valuable to preceptors and to students.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been several attempts to assess the role of pharmacists in the medication reconciliation process during TOC ( Mazhar et al, 2017 , Elamin et al, 2021 , Aljumah, 2013 ), the involvement of pharmacy interns has been given less attention ( Bawazeer et al, 2021 ). Only a few studies have evaluated the effect of pharmacy interns on TOC activities which have shown that interns can be effective in conducting this service, in addition to enhancing their confidence and clinical skills ( Walker et al, 2010 , McLaughlin et al, 2015 , Champion et al, 2019 , Andrus and Stevenson, 2015 , Hertig et al, 2017 ). Therefore, this study aimed to describe and assess the pharmacy intern-led TOC service in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%